Avaliação financeira: estudo de caso em uma empresa de embalagens plásticas de Manaus – AM - Simões, Laura Maia (2019)
This article aims to carry out a financial evaluation in a plastic packaging company in the city of Manaus-AM, for 2017 and 2018. It is understood that the financial department of an organization is a fundamental piece to help the manager in the decision-making or planning process. Moreover, for some organizations, financial statements are viewed as an accounting tool only and as a useful source of data to inform managerial decisions that would be significant for these processes. The current study is valuable since, if a financial assessment is carried out using economic and financial indices, it is possible to collect information about the institution's health and can be leveraged to perform an effective diagnosis of the 2 business reality that will support coherent planning. Regarding its methodology, the research qualifies as descriptive as to its purposes and as quali-quantitative as to its nature. The results showed an unsatisfactory financial situation, since no favorable liquidity indicator could even support that the organization is solvent. It was also observed that its debt is mostly short-term, and its profitability indicators are not favorable, which can trigger short and long term financial problems.